Epidemiological profile of Kala-azar in a tertiary care center of Mid Western Nepal - Mandal, Rajesh Kumar; Pande, Rajan; Karki, Jiwan; Bajracharya, Sandeep Raj; Malla, Vivek; Subedi, Prashant (Journal of Advances in Internal Medicine, 2023)
BACKGROUND Kala-azar has been endemic in the central and eastern Terai region of Nepal neighbouring North Bihar, India. Data of Kala-azar in Mid and Far Western Nepal is scarce. We conducted this study to highlight the burden of Kala-azar in this region. METHODS This study was a cross sectional study conducted from July 2019 to May 2023 in the Department of Internal Medicine of Bheri Hospital. A total of 112 patients diagnosed with Kala-azar were enrolled in study. Data about socio-demographic profile and outcome were entered in MS EXCEL and analyzed by SPSS 20. RESULTS A total of 112 patients were enrolled in study with female predominance 86 (76.79%). Majority of the patients 37(33.03%) were of less than 15 years of age. Kala-azar cases were distributed not only to Terai districts but also in hilly and mountainous districts of Karnali and Sudur paschim provinces. 95(84.82%) cases were new and 17 cases were relapsed cases. 98(87.50%) cases improved with treatment, 5(4.46%) cases expired while one case was referred. CONCLUSIONS Kala-azar is a neglected tropical disease in Nepal. Once confined to the tropical Terai region, it has now been moving towards hills and mountains of Mid and Far Western Nepal. Public awareness campaign and strengthening the Kala-azar treatment centers would help to attain the goal of Kala-azar elimination program of Nepal.